La lógica emocional y afectiva en la investigación educativa - Mendoza Velazco, Derling Jose (2019)
The use of information and communication technologies in university education motivated the present investigation, whose objective was to elaborate a theoretical approach of emotional and affective logic in educational research. The nature of the research was developed under the qualitative approach, based on the interpretative-humanist paradigm. Due to its qualitative scheme, Iberoamerican University of Ecuador UNIB.E has a population of 650 students, of which the homogeneous sample selection was applied, obtaining the participation of ten (10) young people. The participatory observation guide and the semi-structured interview were used as tools for information gathering, the results were analyzed through the generalized triangulation of data and theories through the Atlas.Ti analytical software, where concluded with a theoretical approach formed by three major constructs: Cognitive influences of information and communication technologies (TIC). Emotional logic and affective bonds